2021
DOI: 10.3389/fgene.2021.740940
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium hominis Phylogenomic Analysis Reveals Separate Lineages With Continental Segregation

Abstract: Cryptosporidium is a leading cause of waterborne outbreaks globally, and Cryptosporidium hominis and C. parvum are the principal cause of human cryptosporidiosis on the planet. Thanks to the advances in Next-Generation Sequencing (NGS) sequencing and bioinformatic software development, more than 100 genomes have been generated in the last decade using a metagenomic-like strategy. This procedure involves the parasite oocyst enrichment from stool samples of infected individuals, NGS sequencing, metagenomic assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Conventional Sanger sequencing is still widely used for typing Cryptosporidium, particularly at the gp60 locus [6,7]. Despite the decreasing cost per base of next-generation sequencing (NGS), metagenomic approaches have been under-utilized for Cryptosporidium detection and typing, but are unparalleled for understanding the extent of mixed infections and transmission dynamics [17][18][19] and in detecting and characterizing the diversity of Cryptosporidium species in water and wastewater [20,21]. Despite the utility and importance of both conventional and NGS typing systems for Cryptosporidium, they are still cost-prohibitive for most low-income countries.…”
Section: Cryptosporidium Detection Methodsmentioning
confidence: 99%
“…Conventional Sanger sequencing is still widely used for typing Cryptosporidium, particularly at the gp60 locus [6,7]. Despite the decreasing cost per base of next-generation sequencing (NGS), metagenomic approaches have been under-utilized for Cryptosporidium detection and typing, but are unparalleled for understanding the extent of mixed infections and transmission dynamics [17][18][19] and in detecting and characterizing the diversity of Cryptosporidium species in water and wastewater [20,21]. Despite the utility and importance of both conventional and NGS typing systems for Cryptosporidium, they are still cost-prohibitive for most low-income countries.…”
Section: Cryptosporidium Detection Methodsmentioning
confidence: 99%
“…The need of documenting ancient sequences of Cryptosporidium is also highlighted by recent works based on modern genomes. These works suggested that after initial diversification following the Cretaceous-Paleogene transition (K-Pg boundary), past human activities in historical times (as transatlantic migrations and sanitation development) may explain the current diversity and distribution of this parasite among humans (Garcia-R and Hayman, 2016;Nader et al, 2019;Cabarcas et al, 2021;Tichkule et al, 2022). These hypotheses may be tested through aDNA recovery as illustrated in the case of other infectious agents as Mycobacterium tuberculosis (Brynildsrud et al, 2018).…”
Section: Paleoparasitological Record Ofmentioning
confidence: 99%
“…A total of 235 whole genome sequence (WGS) datasets of C. hominis, C. parvum, and C. cuniculus were downloaded from the Sequence Read Archive (SRA) database of the National Center for Biotechnology Information (NCBI) (https://www.ncbi.nlm.nih.gov/sra/). They were generated in published studies [8][9][10][11][44][45][46][47][48][49][50][51] . Some basic information about the WGS data is provided in Table S1.…”
Section: Cryptosporidium Isolates and Micementioning
confidence: 99%